Temperature induces brain-intake shift of recombinant high-density lipoprotein after traumatic brain injury - Jialin Huang; Yidong Peng; Xin Wang; Xiaokun Gu; Yao Yi; Wenye Wang; Zhenghui He; Zixuan Ma; Qiyuan Feng; Wenlan Qi; Jiyuan Hui; Ru Gong; et al. (Journal of Nanobiotechnology)
Abstract Traumatic brain injury (TBI) is one of the leading public health concerns in the world. Therapeutic hypothermia is routinely used in severe TBI, and pathophysiological hyperthermia, frequently observed in TBI patients, has an unclear impact on drug transport in the injured brain due to a lack of study on its effects. We investigated the effect of post-traumatic therapeutic hypothermia at 33°C and pathophysiological hyperthermia at 39°C on brain transport and cell uptake of neuroprotectants after TBI. Recombinant high-density lipoprotein (rHDL), which possesses anti-inflammatory, antioxidant activity, and blood–brain barrier (BBB) permeability, was chosen as the model drug. First, we found that mild hypothermia and hyperthermia impaired rHDL transport to the brain and lesion targeting in controlled cortical impact mice. Second, we investigated the temperature-induced rHDL uptake shift by various brain cell types. Mild hypothermia impeded the uptake of rHDL by endothelial cells, neurons, microglia, and astrocytes. Hyperthermia impeded the uptake of rHDL by endothelial cells and neurons while promoting its uptake by microglia and astrocytes. In an attempt to understand the mechanisms behind the above phenomena, it was found that temperature induced brain-intake shift of rHDL through the regulation of low-density lipoprotein receptor (LDLR) and LDLR-related protein 1 (LRP1) stability in brain cells. We therefore reported the full view of the temperature-induced brain-intake shift of rHDL after TBI for the first time. It would be of help in coordinating pharmacotherapy with temperature management in individualization and precision medicine. Graphical Abstract